2018
DOI: 10.1016/j.ijcard.2018.08.083
|View full text |Cite
|
Sign up to set email alerts
|

Definition, clinical classification and initial diagnosis of pulmonary hypertension: Updated recommendations from the Cologne Consensus Conference 2018

Abstract: In the summer of 2016, delegates from the German Society of Cardiology (DGK), the German Respiratory Society (DGP), and the German Society of Pediatric Cardiology (DGPK) met in Cologne, Germany, to define consensus-based practice recommendations for the management of patients with pulmonary hypertension (PH). These recommendations were built on the 2015 European Pulmonary Hypertension guidelines, aiming at their practical implementation, considering country-specific issues, and including new evidence, where av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
19

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 101 publications
(100 reference statements)
0
44
0
19
Order By: Relevance
“…As there are no published randomized controlled trials for the specific treatment of these subjects with PAH medications, currently no such treatment is generally recommended or approved. Close follow‐up and, if possible, inclusion into clinical trials has been suggested . In specific subgroups, such as symptomatic patients with systemic sclerosis, PAH therapy may be initiated on an individual basis.…”
Section: Management Of Patients With Mild Pulmonary Arterial Pressurementioning
confidence: 99%
“…As there are no published randomized controlled trials for the specific treatment of these subjects with PAH medications, currently no such treatment is generally recommended or approved. Close follow‐up and, if possible, inclusion into clinical trials has been suggested . In specific subgroups, such as symptomatic patients with systemic sclerosis, PAH therapy may be initiated on an individual basis.…”
Section: Management Of Patients With Mild Pulmonary Arterial Pressurementioning
confidence: 99%
“…45 Pulmonary arterial hypertension (PAH) is a subgroup of PH, identified as class I. PAH is a primary disease of the blood vessels of the lungs: modifica-tions in the vessels structure and functionality are directly responsible of the elevation in pressure. 46 In healthy individuals, mPAP is around 14 mm Hg, with an upper limit of 20 mm Hg. The clinical significance of mPAP between 21 and 24 mm Hg is still uncertain; it might potentially identify subjects at risk of developing PH.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…mPAP can be directly assessed exclusively by right heart catheterization (RHC), which thus is the gold standard for diagnosis. 46 Transthoracic echocardiography, which is performed as screening in all patients with a clinical suspicion of PH, provides an estimate of systolic PAP based on tricuspid regurgitation peak velocity. In addition, RHC allows differentiating precapillary and postcapillary PH taking into consideration hemodynamic parameters as mean pulmonary-capillary wedge pressure, left ventricular end-diastolic pressure, and pulmonary vascular resistance.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…eine rechtsventrikuläre Dysfunktion vorliegt [46]. Koexistieren COPD und Linksherzinsuffizienz, so muss mit einer CpcPH gerechnet werden, die nicht einfach zu diagnostizieren ist [27,42].…”
Section: Akute Situationunclassified